Treatment of iatrogenic injuries of the main bile duct - Praderi, Raúl; Mazza, Milton; Gomez Fossati, Carlos; Estefan, Alberto (Cirugía del Uruguay, 1978)
This series of 41 po·st-operative injuries of the bile ducts reviews the authors' experience on the subject. There is an analysis of such lesions in 4 different situations: 1) Recent wound recognized and repaired during surgery; 2) Immediate postoperatory fistula, peritonitis or stenosis; 3) Media te stricture; 4) Late stenosis with cirrhosis. Treatment consisted in biliary reconstruction in 7 cases; hepaticojejunostomy using Couinaud-Hepp's technique, in 27 cases; and hepaticoduodenostomies in 5 cases, 3 of which had Billroth II gastrectomies. One choledoco-duodenal fistula was not re operated; another patient died without being subject to biliary tract surgery. Operatory death-rate was 7. 6 % in patients reoperated fer biliary tract lesions. Anastomoses were calibrated by transhepatic Tubes or seton tubes ( Y por double O), with the exception of excessively simply cases.